Efektivitas Pengembangan Profesionalisme Guru Melalui Komunitas Belajar Di SDN 1 Trembes Kecamatan Gunem, Kabupaten Rembang - Makarim F, Ummil; Pujiningsih, Ari; Khanifah, Siti; Nurkolis, Nurkolis (Cetta: Jurnal Ilmu Pendidikan, 2025)
Teacher professionalism is a crucial factor in improving the quality of education, especially in responding to the challenges and demands of the times. One of the efforts made to enhance teacher professionalism is through the establishment of learning communities within schools. This study aims to determine the effectiveness of teacher professionalism development through learning communities at SDN 1 Trembes, Gunem District, Rembang Regency. This research uses a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The research subjects included the principal, teachers, and other related parties directly involved in the implementation of the learning community. The results show that the learning community has a positive impact on improving teachers’ pedagogical, professional, social, and personal competencies. Teachers who actively participate in the learning community demonstrate increased confidence, creativity in teaching, and openness to instructional innovation. Supporting factors in the implementation of the learning community include principal support, teacher collaboration, and access to learning resources. Meanwhile, obstacles found include limited time, uneven motivation, lack of facilities, and the absence of a structured evaluation system. In conclusion, the learning community at SDN 1 Trembes is effective in improving teacher professionalism, but its effectiveness greatly depends on the active involvement of teachers and continuous support from the school environment.